Understanding COVID-19: A Hybrid Threat and Its Impact on Sport Mega-Events. A Focus on Japan and the Tokyo 2020 Olympic Games - Ilevbare, Solomon Imoudu; McPherson, Gayle (Frontiers in Sports and Active Living, 2022)
The spread of the coronavirus (Covid-19) pandemic in 2020 affected the sports industry with the cancellation of many professional sports competitions worldwide. Thus, the postponement and organisation of the Tokyo 2020 Olympic Games behind closed doors became a significant disruption to the global sports landscape. In this paper, we present a novel, conceptual discussion, signifying and defining the pandemic via the concept of international security as a hybrid threat (Balaban & Mielniczek, 2018; Wither, 2016). We associated the term hybrid threat to clarify better the difficult times facing sport mega-events. First, the paper proffers that the Covid-19 pandemic is a form of hybrid threat while reflecting on the connected implications of using sport as a soft power tool for nations (Nye, 2009; Portland, 2019; McPherson & Ilevbare, 2021). Secondly, we discuss the impact of Covid-19 on sport mega-events globally and explain the implications of Covid-19 on the Tokyo 2020 summer Olympic Games. This paper although drawing on some figures associated with Covid-19 and the Tokyo Olympic Games presents a theoretical contribution to knowledge in the area of sport mega events, soft power and hybrid threat. We outline how the threats, triggered by the pandemic, have impeded a successful Olympic Games and clarify how these threats have affected Japan's opportunity to use the Games as a soft power tool, which is the paper’s key contribution to the field.